HUBUNGAN KARAKTERISTIK DENGAN HIPERTENSI PADA WANITA USIA SUBUR DI POSBINDU “BERAS SELAWE” - Tri Anasari; Ulfa Fadilla Rudatiningtyas (Ensiklopedia of Journal, 2026)
Hypertension is known as the "silent killer" because it generally develops without specific signs or symptoms, often only being detected after complications have developed. Based on the Banyumas Regency Health Profile for 2023 and 2024, the number of hypertension cases among residents aged 15 years and older in Banyumas Regency was recorded at 169,460 in 2024 and 158,687 in 2025, with a higher proportion of sufferers being female. Meanwhile, data from the Bergas Waras Selawase Integrated Guidance Post (Posbindu) in 2024 showed that of the 143 participants who underwent examination, 50 (34.9%) were diagnosed with hypertension. The incidence of hypertension is influenced by various factors, including age, gender, education level, occupation, family history, dietary patterns, smoking habits, and obesity. This study used a descriptive analytical design with a case-control approach to analyze the relationship between these factors and the incidence of hypertension. A sample size of 56 people was selected using simple random sampling. Data were analyzed using univariate and bivariate analyses with the chi-square test. The results of this study indicate that the majority of respondents had a high level of education (35%, 62.5%), were employed (32%, 57.1%), had a normal waist circumference (31%, 55.4%), and there was a relationship between occupation and waist circumference with hypertension. There was no relationship between education level and hypertension among women of childbearing age at the Beras Selawe Posbindu.Keywords: Characteristics, Hypertension, Women Of Childbearing Age